Analisysis Of The Influence Of Company Size, Liquidity Ratio, and Operating Expense Ratio On Probability Levels Of Islamic Insurance Companies In Indonesia For The 2017 – 2021 Periode - Devi, Yulistia; Ulfah, Ghina; Kurniawan, Agus; Diah Mukminatul (Al-Mashrof: Islamic Banking and Finance, 2023)
This research aims to determine the influence of company size, liquidity ratio, and operating expense ratio partially and simultaneously on the profitability of Islamic insurance companies in Indonesia for the 2017-2021 period and discuss the profitability of Islamic insurance companies from an Islamic economic perspective. The data analysis consists of descriptive statistical analysis and panel data regression techniques with Eviews 12 sv software. Using a purposive sampling technique, the research sample consisted of 20 Islamic insurance companies in Indonesia from 2017-2021. The research results showed that only company size influences profitability (ROE). The influence showed a significant positive effect. Meanwhile, the liquidity and operating expense ratios do not affect profitability (ROE). Meanwhile, these three variables simultaneously influenced Islamic insurance companies' profitability (ROE) in Indonesia in 2017-2021. Then, the profitability of Islamic insurance companies from an Islamic economic perspective not only considers ways to gain profits but also aspects of the blessings and pleasure of Allah SWT so that it is not only worldly profits but falah or prosperity in the world and the hereafter. Keywords: Islamic Insurance, Profitability, Operating Expense Ratio, Liquidity Ratio, and Company Size